Establishment of a selective evaluation method for DPP4 inhibitors based on recombinant human DPP8 and DPP9 proteins - Jinglong Liu; Yi Huan; Caina Li; Minzhi Liu; Zhufang Shen (Elsevier, 2014)
Dipeptidyl peptidase 4 (DPP4) is recognised as an attractive anti-diabetic drug target, and several DPP4 inhibitors are already on the market. As members of the same gene family, dipeptidyl peptidase 8 (DPP8) and dipeptidyl peptidase 9 (DPP9) share high sequence and structural homology as well as functional activity with DPP4. However, the inhibition of their activities was reported to cause severe toxicities. Thus, the development of DPP4 inhibitors that do not have DPP8 and DPP9 inhibitory activity is critical for safe anti-diabetic therapy. To achieve this goal, we established a selective evaluation method for DPP4 inhibitors based on recombinant human DPP8 and DPP9 proteins expressed by Rosetta cells. In this method, we used purified recombinant 120 kDa DPP8 or DPP9 protein from the Rosetta expression system. The optimum concentrations of the recombinant DPP8 and DPP9 proteins were 30 ng/mL and 20 ng/mL, respectively, and the corresponding concentrations of their substrates were both 0.2 mmol/L. This method was highly reproducible and reliable for the evaluation of the DPP8 and DPP9 selectivity for DPP4 inhibitor candidates, which would provide valuable guidance in the development of safe DPP4 inhibitors.